Factors Influencing Vegetable Consumption Among Floridians: An Exploratory Study - Pablo Lamino; Rafael Landaverde; Jean A Parrella; Amy Boren-Alpizar; John M. Diaz (Journal of Applied Communications, 2025)
Vegetable consumption plays a vital role in promoting health and preventing disease, yet intake remains below recommended levels across the United States, particularly in Florida, a major vegetable-producing state. Drawing on the Theory of Planned Behavior, this research examined Floridian consumers' vegetable purchasing behaviors and preferences, focusing on the influence of demographic, social, and contextual factors. Data were collected through a cross-sectional online survey of 756 residents, selected via quota sampling to reflect variation across age, gender, ethnicity, education, occupation, and political beliefs. Participants responded to a structured questionnaire assessing demographic characteristics, purchasing patterns, and vegetable preferences. Multiple linear regression analysis identified key predictors of vegetable expenditures, while principal component analysis revealed underlying patterns in preferred vegetable qualities. Findings indicate that freshness was the most valued attribute, with supermarkets serving as the primary source of vegetables. Broccoli and lettuce emerged as the most frequently consumed vegetables. Higher expenditures were associated with being female, African American, a homemaker, and with preferences for fresh and organic options. Notably, organic and non-GMO attributes accounted for a significant portion of consumer choices. These insights offer valuable guidance for designing targeted communication and policy interventions to enhance vegetable accessibility and dietary diversity. Addressing demographic disparities in vegetable consumption can contribute to more effective public health strategies and market development efforts in Florida and similar contexts.
Keywords: Florida consumers; vegetables; public perceptions; purchasing behaviors